Jual Beli Tanah Adat di Hadapan Kepala Desa Bantang Kecamatan Kintamani Kabupaten Bangli - I Made Suamba; I Made Suwitra; Dyah Gayatri Sudibya (Jurnal Analogi Hukum, 2019)
Earth constitutes a part inherent with human life and common law society. A Man and common law society in its life so pending with earth, since the earth constitutes place based on, the place looks for subsistence and also the last resort if that man passes away. Still makes sense aboveground rights earth, merchant at front carries the wind village. According to bases Section 37 sentences (i) Commanding regulations No. 24 Years 1997 about Cadastral, soiled transition bases sell just buy is listed if proved by deed that made by PPAT in charge terminological legislation regulation rule that prevailing. The formulation of the problem in this study is 1. How is the settlement of buying and selling customary land in the village of Bantang, Kintamani District, Bangli Regency? 2. What is the form of legal protection for buying and selling customary land in front of the Bantang village head, Kintamani District, Bangli Regency?This research assessed by the empirical method bases fact, those are in the field and information of village party on duty and Custom at silvan Bantang and is assessed and analysis bases prevailing legislative intent for now basic sentences and also protection form sentence of custom earth merchant, soiled merchant performing custom is before carry the wind Village at Silvan Bantang Kintamani's district, Bangli's regency. Law preventives protection in this case is proved with paying receipt gets stamp duty arid deponents and make sense repressives protections passes through to shut close villages and letter of attorney gets a stamp.